TANTANGAN PENGEMBANGAN SISTEM PENGELOLAAN SAMPAH YANG BERKELANJUTAN DI PEMERINTAH KABUPATEN BATANG - Setiawan, Hendy; Arief Widodo, Sulkhan (Bapelitbang Kabupaten Batang, 2025)
The purpose of this paper is to discuss the challenges of sustainable waste management in Batang Regency. The challenges of waste management in Batang Regency are a serious issue that must be resolved. This is because the increasing volume of waste every year is not balanced by good management. This situation is reinforced by the availability of limited infrastructure and also the low cultural conditions of the community. Therefore, in the midst of the waste problem, it is important to see the challenges faced by the Batang Regency Government in handling waste management when the Randukuning TPA is overloaded. This study uses a literature review, where researchers use secondary data to answer the problem formulation. The data were collected and selected from various media, writings, journals, or other secondary sources and analyzed using the Milles and Hubberman qualitative analysis method. The results of the study indicate that the challenges of waste management in Batang Regency still cannot get an ideal solution. This is considering the various limitations and lack of supporting suggestions so that waste to this day has not been fully resolved with a long-term solution. In addition, the strategy played by the Batang Regency Government is still not focused on education and the formation of community behavior patterns in managing household waste independently. These challenges are becoming increasingly complex, requiring other alternatives in waste management in Batang Regency Government.